Agreement on Symptoms Between Children With Ulcerative Colitis and Their Caregivers: Towards Developing the TUMMY-UC. Issue 2 (August 2021) - Marcovitch, Liron; Focht, Gili; Horesh, Anat; Shosberger, Adi; Hyams, Jeffrey; Bousvaros, Athos; Hale, Amy E.; Baldassano, Robert; Otley, Anthony; Mack, David R.; Kappelman, Michael D.; Griffiths, Anne M.; et al.
Abstract : ABSTRACT: As part of the development of the TUMMY-UC, a patient-reported outcome (PRO) measure for pediatric ulcerative colitis (UC), we aimed to explore agreement on UC symptoms between children and their caregivers. We conducted 44 interviews with children ages 8–12 years, who completed the PRO version of the TUMMY-UC, and their caregivers, who completed the observer-reported outcome (obsRO) version. There was excellent agreement between the total TUMMY-UC PRO and obsRO scores (intra-class correlation coefficient = 0.92 [95% confidence interval 0.74–0.98]). The obsRO scores were always within the same disease-activity category as the corresponding PRO score (ie, remission, mild and moderate-severe disease). There was a strong correlation of the TUMMY-UC PRO and obsRO scores with physician global assessment of disease activity ( r = 0.94 and r = 0.90, respectively, P < 0.001) and the pediatric UC activity index ( r = 0.95 and r = 0.96; P < 0.001). These data support conceptual equivalence between the PRO and obsRO TUMMY-UC versions, and provide support for their incorporation into one score.